Voluntary Fair Value Disclosures Beyond SFAS 157’s Three-level Estimates - CHUNG, Sung Gon (Institutional Knowledge at Singapore Management University, 2017)
Some firms voluntarily make disclosures about the controls and processes in place to ensure the reliability of fair value estimates. Consistent with these disclosures being driven by management’s concerns about the reliability of their SFAS 157 estimates, we find that firms with more opaque estimates are more likely to provide such disclosures. We then examine whether these disclosures increase the reliability of fair value estimates. We find that they are associated with higher market pricing and lower information risk for Level 3 estimates. Further analyses of the contents of the reliability disclosures reveal that the following are particularly important to investors: discussions about the external and independent pricing of fair value estimates as well as proper classification of the estimates according to the SFAS 157 hierarchy. Overall, our results suggest that the voluntary reliability disclosures that firms provide beyond SFAS 157’s three-level estimates help reduce investors’ uncertainty about more opaque fair value estimates.